Implementation Of Forward Chaining Expert System To Identify Facial Skin Types In Determining Facial Beauty Treatments - Anam, Khairil; Irawan, Nico; Homaidi, Ahmad (International Journal of Health and Information System, 2023)
Skin is part of the outer layer of the human body which is flexible, soft and sensitive and is the first line of defense from various germs, viruses, bacteria and what is very important and the main part is facial skin, therefore we must keep it healthy, fresh and clean by determining proper beauty facial treatment. This research was conducted to design and create an expert system capable of identifying facial skin types to determine facial beauty treatments. Making this expert system using forward chaining method. The result of this research is an application that can help make it easier for users to determine facial facial treatments without having to queue and wait for consultations with a beauty doctor, so that they can immediately determine the appropriate type of skin facial treatment through the Android application.